Chinese culture “Going Out” through translating Chinese culinary culture : a bite of China Ⅱ, a case study - Huang, Siqi (Nanyang Technological University, 2020)
This dissertation is a translative study of Chinese culinary culture through the perspective of China’s intercultural publicity. Chinese culinary culture is often an area of general interest to foreign audiences since Chinese food is readily available.